INTEGRATION OF THE HEUTAGOGY APPROACH AND WORDWALL MEDIA IN HOLIDAY CONVERSATION LEARNING TO IMPROVE THE LEARNING INDEPENDENCE OF GRADE V ICP STUDENTS - Wina Kartika Bidari; Yulianto Sabat; Sulistyaningsih; Eka Fadilah (Universitas Muhammadiyah Makassar, 2026)
The purpose of this study is to describe how the integration of the heutagogy approach and the digital media Wordwall can encourage independent learning in grade V ICP students. This study uses a descriptive qualitative method with data collection techniques through observation, documentation, and in-depth interviews with key informants namely the English teacher of grade V ICP, one student with a high level of learning independence, and one student with a medium low level of learning independence. The results show that the application of Wordwall in Holiday conversation learning provides space for students to learn flexibly, choose activities according to their needs, access materials independently, and conduct self-evaluations based on the results displayed automatically by the system. In addition to increasing learning engagement, Wordwall also forms a reflective attitude and student initiative in learning, thereby encouraging the growth of independent learning in line with the principles of heutagogy. This study recommends the integration of pedagogical strategies and digital media as an effective learning approach in building the character of independent learners from an early age.